Acriflavine, a HIF-1 inhibitor, preserves vision in an experimental autoimmune encephalomyelitis model of optic neuritis - Anders, Jeffrey J.; Elwood, Benjamin W.; Kardon, Randy H.; Gramlich, Oliver W. (Frontiers in Immunology, 2023)
Optic neuritis (ON) is often an early sign of multiple sclerosis (MS), and recent studies show a link between HIF-1 pathway activation and inflammation. This study aimed to determine if inhibition of the HIF-1 pathway using the HIF-1α antagonist Acriflavine (ACF) can reduce clinical progression and rescue the ocular phenotype in an experimental autoimmune encephalomyelitis (EAE) ON model. EAE-related ON was induced in 60 female C57BL/6J mice by immunization with MOG33-55, and 20 EAE mice received daily systemic injections of ACF at 5 mg/kg. Changes in visual function and structure of ACF-treated EAE mice were compared to those of placebo-injected EAE mice and naive control mice. ACF treatment improved motor sensory impairment along with preserving visual acuity and optic nerve function. Analysis of retinal ganglion cell complex also showed preserved thickness correlating with increased survival of retinal ganglion cells and their axons. Optic nerve cell infiltration and magnitude of demyelination were decreased in ACF-treated EAE mice. Subsequent in vitro studies revealed improvements not only attributed to the inhibition of HIF-1 but also to previously unappreciated interaction with the eIF2a/ATF4 axis in the unfolded protein response pathway. In conclusion, this study suggests that ACF treatment is effective in an animal model of MS via its pleiotropic effects on inhibition of HIF-1 and UPR signaling, and may be a viable approach to promote rehabilitation in MS.